DEVELOPMENT OF A MODEL FOR INTEGRATING GREEN SKILLS INTO THE VOCATIONAL FASHION DESIGN CURRICULUM TO SUPPORT EMPLOYABILITY IN THE SUSTAINABLE FASHION INDUSTRY - Novia Nailatun Nufus; Agus Hery Supadmi Irianti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The transition toward a green economy has significantly transformed various industrial sectors, including the fashion industry, which is recognized as one of the largest contributors to environmental degradation. This condition requires a workforce equipped with green skills to support sustainable industry practices. Vocational education plays a strategic role in preparing graduates for these demands; however, the integration of green skills into vocational curricula remains limited. This study aims to develop a conceptual model for integrating green skills into the vocational fashion curriculum to enhance work readiness in the sustainable fashion industry. This study employs a qualitative approach using a literature review method. The findings reveal that the proposed model consists of four main components: sustainability-based curriculum content, project-based learning strategies, industry collaboration, and competency-based assessment. The model is expected to improve curriculum relevance and strengthen graduates’ work readiness.